Archaeology and Identity In the 19th Century Northern Cape Frontier: the Xhosa of the Pramberg - Zachariou, Nicholas Alexander (Department of Archaeology, 2020)
This dissertation examines the identity of the Xhosa communities that settled in the frontier zone of the Northern Cape during the first half of the 19th century. It does this through the archaeology, and ethnographic and historical accounts. The concept of a baseline Nguni identity in the Eastern Cape is examined with an emphasis on settlement, mobility and cultural interaction. The historical background and a brief history of the of the Xhosa in the Northern Cape will be detailed, focusing on the Pramberg community. The archaeology of three Xhosa sites in the Pramberg will be described and analysed, and then contrasted and compared with the ethnographic and historical evidence. The result of this comparison is a discussion of the identity change and continuity of the Pramberg Xhosa in the context of the cultural milieu of the frontier and the appropriation of land by the expanding Cape colony.